Sales Performance Optimization: Information Technology Impact Over Sales Force Effectiveness (SFE) In Pharmaceutical Industry Malaysia - Lim, Kean Hoe (2008)
According to pharmaceutical industry estimates, a company's biggest investment in this industry is its sales force. Although the correlation of pharmaceutical sales and the sales force activities is widely studied, with the recent extensive stidies of SFE (Sales Force Effectiveness) and SFA (Sales Force Automation), suggesting companies should invest heavily on SFA system or look in to training to improve SFE, which are focused heavily on Qualitative Aspects.